Unusual manifestations of malaria in children - Agarwal, Neha; Taneja, Sunil (International Journal of Contemporary Pediatrics, 2021)
Background: Till recently, vivax malaria was being regarded as a “benign” disease. Falciparum malaria is known to be a serious illness with life threatening complications as cerebral malaria, jaundice, acute kidney injury, metabolic acidosis and bleeding diatheses. Recently, some other atypical presentations are also being noted which have hardly been discussed previously. The present report highlights the various unusual presentations of malaria in children. Methods: The study design was hospital based prospective observational study conducted over one year. Children between the ages of 1 month to 18 years admitted with a diagnosis of malaria confirmed by peripheral blood smear examination and/or rapid diagnostic test having unusual manifestations were studied. Patients with dengue fever, enteric fever, viral hepatitis, or any other concomitant infection were excluded. The various unusual manifestations of malaria, disease course and outcome were analysed. Results: 58 (27.1%) out of 214 patients studied were found to have atypical manifestations. The unusual features observed were ARDS in vivax malaria (n=11), fulminant hepatic failure (n=5), post malaria neurological syndrome (n=3), stroke (n=3), bilateral optic neuritis (n=1), abducens nerve palsy (n=1), autoimmune haemolytic anemia (n=1), nephrotic syndrome (n=1), splenic infarction (n=2), acute abdomen (n=2), hemiplegia (n=2), psychomotor agitation (n=7), sepsis (n=5), shock (n=3), disseminated intravascular coagulation (n=3) and urticaria (n=2). Six children with vivax presented in deep coma. Conclusions: Clinicians in endemic areas should be aware of unusual and varied presentations of malaria; failure of recognition of which may lead to delayed diagnosis resulting in increased mortality.